Babel Karya R, F Kuang dalam Pandangan Hegemoni Gramsci - Nur Fadillah Dwi Jayanti (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
This abstract discusses the application of Antonio Gramsci’s theory of hegemony in R.F. Kuang’s novel Babel. This study highlights how the concept of hegemony, particularly the ideological control of the ruling class, is represented in the social and educational structures depicted in the story. This form of hegemony is reflected through the academic institution of Oxford University and the Babel magic department, which function as tools for the reproduction of knowledge as well as the legitimization of colonial power. Through Gramsci’s theoretical approach, this analysis shows that power is not only exercised through coercion but also through consent constructed ideologically within educational and linguistic systems. In addition, this study examines the role of intellectuals in resisting such hegemony. The characters Robin and his companions are portrayed as developing critical awareness and solidarity as a form of resistance against the injustice they face. Thus, Babel illustrates the complex dynamics between domination and resistance, as well as how intellectuals may play a role in both maintaining and challenging dominant ideology. This study emphasizes the relevance of Gramsci’s theory in understanding power relations, resistance, and the production of ideology in literary works.